Changes in urinary metabolic profiles of colorectal cancer patients enrolled in a prospective cohort study (ColoCare) - Liesenfeld, David; Habermann, Nina; Toth, Reka; Owen, Robert; Frei, Eva; Böhm, Jürgen; Schrotz-King, Petra; Klika, Karel D.; Ulrich, Cornelia (Metabolomics, 2015)
Metabolomics is a valuable tool for biomarker screening of colorectal cancer (CRC). In this study, we profiled the urinary metabolomes of patients enrolled in a prospective patient cohort (ColoCare). We aimed to determine changes in the metabolome of the longer clinical follow-up and ascertain candidate markers with possibly prognostic significance.